Graphical Materials as Teaching Tools for the Conceptualization of Space - Fridl, Jerneja (ZRC SAZU, Založba ZRC, 2007)
Didactic publication is just one of the results of an international project R.A.V.E Space, which aims with young people to raise the awareness of values of space through the process of education. The state of the space and the changes that have occurred within in it over extended time periods can be most easily found out using a variety of graphical materials. Among these, cartographic and photographic materials, in classical or electronic form, stand out and form an indispensable tool in teaching young people about space and its importance for the continuing development of society. We highlight in particular the use of different maps, aerial photos, three-dimensional and simulated models and photographs of an area from different time periods. We have presented a selection of cartographic and other graphical teaching tools at seminars for teachers, showing how they can be used to teach pupils about the significance and role of space for sustainable development.